2020
DOI: 10.1007/s00192-020-04594-w
|View full text |Cite
|
Sign up to set email alerts
|

Do you really want to deactivate your sacral neuromodulation device during pregnancy? A single center case series

Abstract: Introduction and hypothesis The main objective of the study is to assess the efficacy and safety of sacral neuromodulation (SNM) during pregnancy. Methods We retrospectively enrolled patients who underwent SNM implantation in our center and subsequently became pregnant. The indication for SNM, timing of device de-activation (if performed), course of pregnancy and urological complications, duration of labor, childbirth term, delivery mode, congenital abnormalities and SNM dysfunctions after delivery were reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Electrical stimulation of the bilateral S1 dorsal roots in rats, where the parasympathetic nerves are located, showed no adverse effects on pregnant rats and foetuses (Wang & Hassouna, 1999). Two reviews (Mahran et al, 2017;Yaiesh et al, 2016) and one case series (Agnello et al, 2021) reported the use of sacral neuromodulation in pregnant patients with bladder dysfunction or faecal incontinence (Agnello et al, 2021;Mahran et al, 2017;Wang & Hassouna, 1999;Yaiesh et al, 2016) are consistent with the current study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Electrical stimulation of the bilateral S1 dorsal roots in rats, where the parasympathetic nerves are located, showed no adverse effects on pregnant rats and foetuses (Wang & Hassouna, 1999). Two reviews (Mahran et al, 2017;Yaiesh et al, 2016) and one case series (Agnello et al, 2021) reported the use of sacral neuromodulation in pregnant patients with bladder dysfunction or faecal incontinence (Agnello et al, 2021;Mahran et al, 2017;Wang & Hassouna, 1999;Yaiesh et al, 2016) are consistent with the current study.…”
Section: Discussionsupporting
confidence: 89%
“…Some women have undergone electrical stimulation therapy even during pregnancy for these disorders. Sacral neuromodulation implantation was shown to be effective for pregnant patients with bladder dysfunction or faecal incontinence and caused no maternal or foetal adverse effects (Agnello et al., 2021; Mahran et al., 2017; Yaiesh et al., 2016); however, electrical stimulation using sacral neuromodulation implantation is invasive. Sacral surface electrical stimulation (ss‐ES) of the skin over the posterior sacral foramen is a non‐invasive method for neuromodulation of the S2–S4 area and has produced similar effects (Yokozuka et al., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…After excluding duplicates, articles only available as abstracts, articles in languages other than English, and articles not related to sacral neuromodulation therapy, only 11 papers remained. Three original animal studies [ 10 , 11 , 12 ], six case reports [ 13 , 14 , 15 , 16 , 17 , 18 ], one systematic review, and one literature review [ 19 , 20 ] were analysed. The case reports included 1 to 14 pregnancies in women treated with SNM.…”
Section: Resultsmentioning
confidence: 99%
“…Of patients who gave birth prematurely, 1 maintained neuromodulation and 8 turned off the IPG. The causes of preterm labour were various: premature uterine contraction, premature detachment of the placenta, recurrent UTIs, chronic symphysis pubis dysfunction, and the need for chemotherapy for breast cancer [ 13 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation